Preserving Academic Integrity in AI-Generated Assessments: A Case Study in Entrepreneurship at a Sino-Foreign University - Ozguven, Mustafa; Vahed, Anisa; Akhal, Khalid; Benitez Garcia, Antonio (African Journal of Inter/Multidisciplinary Studies, 2024)
Integrating Artificial Intelligence (AI) in higher education presents opportunities and ethical challenges, particularly regarding the increase in students submitting AI-generated assessments. This trend calls for ethical engagement from faculty and students to ensure that AI supports learning without diminishing cognitive skills. Despite existing academic integrity policies, the complexities of AI introduce new dilemmas, often blurring the lines of misconduct and unintentional deception. Focusing on a Chinese-British Sino-Foreign university where students used increasing amounts of AI- generated content from ChatGPT in their Entrepreneurship project, the study emphasises the necessity of critically evaluating AI-generated content due to potential biases and ethical concerns. Through qualitative interviews with 24 participants from the university's Entrepreneurship and Enterprise Hub, issues of transparency, fairness, and policy development emerged as central themes. The findings emphasize the need for a structured, culturally sensitive approach to AI integration. A proposed curriculum matrix aims to facilitate responsible AI usage, supporting faculty in promoting ethical standards while preparing students for a tech-driven workforce. The study concludes by advocating for ongoing dialogue and professional development to foster responsible AI practices in education, ultimately enhancing critical thinking and ethical decision-making in entrepreneurship.